Risk factors for disruptions in tuberculosis care in Uganda during the COVID-19 pandemic. - Peter D Jackson; Stella Zawedde Muyanja; Isaac Sekitoleko; Mudarshiru Bbuye; Madeline Helwig; Roma Padalkar; Mariam Hammad; Dennis Hopkinson; Trishul Siddharthan (Public Library of Science (PLoS), 2023)
Background During the COVID-19 pandemic, TB mortality increased while diagnoses decreased, likely due to care disruption. In March, 2020, Uganda-a country with high TB burden, implemented a COVID-19 lockdown with associated decrease in TB diagnoses. This study aims to examine patient level risk factors for disruption in TB care during the COVID-19 pandemic in Uganda. This retrospective cross-sectional cohort study included six TB clinics in Uganda. Clustered sampling included phases of TB care and three time-periods: pre-lockdown, lockdown and post-lockdown. Characteristics of patients with TB care disruption (TBCD), defined as those with > 2 months of symptoms prior to diagnosis or who missed a TB clinic, and those without TB care disruption (non-TBCD) were analyzed between time-periods. 1,624 charts were reviewed; 1322 were contacted, 672 consented and completed phone interview; pre-lockdown (n = 213), lockdown (n = 189) and post-lockdown (n = 270). TBCD occurred in 57% (385/672) of patients. There was an increase in the proportion of urban patients in the TBCD and non-TBCD groups during post-lockdown (p <0.001). There was no difference in demographics, HIV co-infection, socioeconomic status, or distance to TB clinic between TBCD and non-TBCD groups or within TBCD by time-period. There were few differences amongst TBCD and all TB patients by time-period. The increase in urban patients' post-lockdown may represent a portion of urban patients who delayed care until post-lockdown. Insignificant trends suggesting more TBCD amongst those who lived further from clinics and those without HIV-coinfection require more investigation.